Dual S-scheme ZnO–g-C3N4–CuO heterosystem: a potential photocatalyst for H2 evolution and wastewater treatment. Issue 5 (1st March 2023) - Ahmad, Irshad; Shukrullah, Shazia; Naz, Muhammad Yasin; Bhatti, Haq Nawaz
Abstract : A ZnO–g-C3 N4 –CuO catalyst prepared by an ecofriendly solution combustion process is used for H2 evolution. The mechanism of H2 evolution over ZnO–g-C3 N4 –CuO is described under visible light illumination. Abstract : S-scheme heterojunctions have acquired rapid momentum in designing novel photocatalysts with prolonged separation of photocarriers while preserving exceptional redox ability, fascinating the scientific community. Herein, a simple solution combustion approach is used to design a ternary ZnO–g-C3 N4 –CuO heterojunction photocatalyst that is used in photocatalytic H2 evolution and degradation of MB and RhB. The maximum rate of MB degradation occurs at 100% under visible light for 35 min, which is noticeably higher than the RhB degradation rate (90%) under identical conditions. According to the trapping experiment, holes and ˙OH radicals are the primary oxidizing species that degraded MB and RhB. In comparison to pure ZnO, ZnO–CuO, and ZnO–g-C3 N4 photocatalysts, the ternary ZnO–g-C3 N4 –CuO composite exhibits an ideal H2 evolution rate of 17.55 mmol −1 h −1 under visible light, which is approximately 42, 1.75, and 1.4 times superior, respectively. Besides, the strongest ZnO–g-C3 N4 –CuO composite undergoes five consecutive runs of stability test, and only a 3% decrease in H2 evolution after those tests reveals the photocatalyst's strong stability. The various analyses reveal that a dual S-scheme photocarrier transfer mode is produced at the interface of the ZnO–g-C3 N4 –CuO composite, providing outstanding separation of photocarriers. In the domain of photocatalysis, the design of this research can provide new insights into designing efficient heterojunction photocatalysts with diverse application potential.